Upaya Mengurangi Skeptisisme Iklan Hijau dalam Meningkatkan Perilaku Pembelian Produk Hijau - Waskito, Jati; Wahyono, Wahyono (Benefit: Jurnal Manajemen dan Bisnis, 2016)
The purpose of this study was to analyze the effect of consumer involvement in environmental sustainability, relevance, confusion, and entertainment from an ad impression of green against the skepticism of consumers through an approach of how far the company can deliver their messages more effectively. Survey by the instrument list of questions to get 299 residents of the city of Solo who participated in the study. The results of multiple regression analysis found that consumer involvement and relevance negative effect on consumer apathy towards green advertising. Variable confusion positive effect on consumer apathy towards green advertising. While variable entertain no significant effect on their skepticism